Multifunctional decorative coatings based on cement-silicate binder - Shaybadullina Arina; Yakovlev Grygory; Grakhov Valery; Polyanskikh Irina; Ginchitskaya Yuliya (MATEC Web of Conferences, 2018)
A facade decorative coating has been developed that is based on sodium silicate and Portland cement and modified with a complex ultra-and nanodispersed admixture including titanium dioxide, expanded perlite sand, and multi-walled carbon nanotubes dispersion. The advantage of the produced coating is using Portland cement as a silicizer instead of the conventionally used zinc oxide. Adding ultra-and nanodispersed admixtures to the cement-silicate composition leads to the structural modification of the matrix of the binder composition along with the formation of a more durable coating (up to 4-5 times compared with the existing analogues) and the possibility of absorbing man-made electromagnetic radiation up to 38%. Expanded pearlite sand in the silicate coating provides a relief surface when applied on the base. The cement-silicate composition for coating facades is shown to have the following physical and technical characteristics: the viscosity measured with Viscometer-6 is 29 sec; the hydrogen index of the medium pH=12.33; the film resistance to static effect of water is 8 hr; the paint consumption for a two-layer coating is 200-400 g/m2; the adhesion (the cross-cut test) is 1 point; the conventional light-fastness is 4-5 points; the frost-resistance of the silicate coating is 75 cycles. The developed facade cement-silicate coating can be applied on the surface of silicate-containing materials. The cost effectiveness of using the multifunctional protectivedecorative coating has been proved in comparison with similar compositions.